A study to assess serum levels of superoxide dismutase and catalase in senile cataract patients with and without diabetes mellitus at tertiary care hospital - Lipa, Mohanty; Madhusmita, Behera; Ajay, Purohit (International Journal of Research in Medical Sciences, 2016)
Background: The objective was to assess the possible relationship of serum levels of superoxide Dismutase and catalase and development of senile cataract in patients with and without diabetes mellitus. Methods: The study was done in the Department of Ophthalmology with support of Department of Biochemistry at Geetanjali Medical College and Hospital, Geetanjali University, Udaipur, Rajasthan. The study has been conducted during the time period of October 2014 and October 2015. Blood samples of 120 senile cataract patients, i.e. 60 with diabetes and 60 without diabetes were taken and levels of superoxide dismutase and catalase were studied. Results: Statistically significant difference in age wise occurrence of cataract was found between diabetic and non-diabetic patients i.e. cataract was found at a later age in senile non diabetic patients as compared with senile diabetic patients (p<0.001). Senile diabetic patients had significantly lower serum level of SOD as compared to senile non diabetic patients (p<0.001 for both). Similarly, senile diabetic patients had significantly lower serum levels of catalase as compared to senile non diabetic patients (p<0.001 for both). Conclusions: Increase in oxidative stress and decrease in anti-oxidant enzyme activities have a role in the early development of cataract in senile patients with diabetes. Thus, diabetic cataract seems to be associated with decrease in serum levels of SOD and catalase.